Long-Term Cognitive Outcomes and Associated Quality of Life of Young Adults Who Experienced Liver Transplantation in Early Childhood - Beath, Sue V.; Taylor, Zoe; Wray, Jo; Passingham, Charlotte; Lloyd, Carla; Kelly, Deirdre A. (Frontiers in Transplantation, 2022)
We evaluated long term outcomes in infants born 1992-2002 with cholestatic liver disease (CLD), who underwent successful Liver transplantation (LT). 160 children with CLD were identified: 68 had developmental assessments before and after LT of whom 32 were excluded because they were followed up elsewhere; 16/36 consented to complete measures of IQ, anxiety, depression, Health Related Quality of Life (HRQoL), and a habits/employment survey. Illness severity and developmental attainment prior to LT were comparable with the 32 excluded and 20 patients who declined to take part. The IQ of young adults after LT (mean score = 91.13, range 75-108, SD 10.4), was not significantly improved compared to Pre-LT scores (mean score = 85.7 range 50-111, SD 17), but was inversely correlated with stunting of growth and duration of disease before LT, highlighting the need for timely LT in CLD. HRQoL scores ranged from 22-99 (mean 64.5 SD 20.7), comparable to scores in other LT recipients. Five (31%) had mild-moderate depression; 5 (31%) had moderate-severe anxiety. associated with reduced HRQoL (p=0.01 and p=0.06 respectively); nine had problematic fatigue which correlated with reduced HRQoL (r2=0.4 p=0.007). Reduced medication adherence was associated with fatigue (Spearman correlation r2=0.267; p=0.09) and anxiety (Spearman correlation r2=0.597; p=0.02). Raised body mass index was also associated with reduced and Health-related quality of life scores PeLTQL© (r2=0.379 p=0.011). Fifteen (94%) were in education or employment. The long-term neuro-cognitive and psychosocial outcomes of young adults transplanted as babies is encouraging, although anxiety/depression were more common than in the healthy population. Psychosocial questionnaires help identify those young adult LT recipients who may benefit from support when moving from pediatrics to adult sector services.